2010
DOI: 10.1136/jech.2009.099879
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of flu vaccination among urban Hispanic children and adults

Abstract: Background Flu vaccination is effective for preventing infection, but coverage levels in the USA remain low—especially among racial/ethnic minorities. This study examines factors associated with flu vaccination in a predominantly Hispanic community in Manhattan, New York. Methods Households were recruited during the 2006–2007 and 2007–2008 flu seasons. Primary household respondents were interviewed to determine knowledge of flu transmission/treatment and vaccination status and demographic information for all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 26 publications
2
24
2
Order By: Relevance
“…Instead, caregiver perceptions about vaccine effectiveness and vaccine safety, consistent with previous studies including Latino populations (9, 2123), played a more prominent role in their influenza vaccination decision. These findings indicate that provider recommendation alone may be insufficient, as suggested recently for the HPV vaccine (24).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Instead, caregiver perceptions about vaccine effectiveness and vaccine safety, consistent with previous studies including Latino populations (9, 2123), played a more prominent role in their influenza vaccination decision. These findings indicate that provider recommendation alone may be insufficient, as suggested recently for the HPV vaccine (24).…”
Section: Discussionsupporting
confidence: 76%
“…The survey instrument was designed based upon expert opinion and prior studies (8, 9). It contained 11 open-ended and 26 closed-ended items with pre-coded responses addressing 1) general attitudes about preventive care and vaccination (e.g., “In general, how important do you think it is for [your child] to be vaccinated?…”
Section: Methodsmentioning
confidence: 99%
“…For example, families with low health literacy have been shown to have distinct vaccine education needs. [34][35][36][37][38] Meeting the needs of this group is particularly important since 90 million Americans have low health literacy 39 with minority and low-income populations at greatest risk. 40 Vaccine interventions in this group ideally should avoid or simplify written materials, two objectives facilitated through the use of health information technology.…”
mentioning
confidence: 99%
“…In addition to not knowing whether or not they should seek influenza vaccinations, some patients, regardless of race, do not know when to be vaccinated, assume healthy people do not need to be vaccinated, are concerned about potential side-effects of the vaccination, or experience other barriers to vaccination (Johnson et al, 2008). Multiple studies have found that Hispanic patients perceive access and cost as barriers to influenza vaccination (Chen et al, 2007; Cohen et al, 2012). Other studies have found that Black and Hispanic patients are more likely than White patients to perceive the influenza vaccination as being ineffective (Wooten et al, 2012) and to think they can get influenza from receiving the vaccine (Chen et al, 2007; Wooten et al, 2012).…”
Section: Barriers To Influenza Vaccinationmentioning
confidence: 99%